Evaluation of Grid Pattern City in Tropical Zone Considering Urban Morphology Viewing from Shading Aspect - Khaing Myint Mo (Lowland Technology International, 2020)
The impact on urban microclimate is basically governed by city morphology, materialization and landscaping of neighborhood. The modification of these parameters, such as city pattern, building facets design, tree pattern and tree species, can help to be healthy urbanism. This paper discusses about the evaluation of grid pattern city in tropical zone, which is aging, but still using as business area considering urban morphology with respect to shading since shading has supreme influence on thermal comfort. The purpose of this research is to investigate shading condition of existing city pattern to know whether the city is still reasonable to live or not by analyzing morphological elements using geographic information system (GIS), 3D modelling program (sketch up), shading analysis tool, quantitative method and statistical analysis. The scheme of this research is divided into two main parts: evaluation by the effect of type of colonial style building facet and evaluation by the effect of tree pattern and different tree species. The result provides hypothesis of urban morphology and appropriate design recommendation for Grid pattern city to maintain old urban area in conformity with tropical zone without vanishing original image of the city